From Biology to Therapy: Improvements of Therapeutic Options in Lung Cancer - Formisano, Luigi; Jansen, Valerie M.; Marciano, Roberta; Bianco, Roberto (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Lung cancer is the leading cause of cancer-related mortality around the world, despite effective chemotherapeutic agents, the prognosis has remained poor for a long time. The discovery of molecular changes that drive lung cancer has led to a dramatic shift in the therapeutic landscape of this disease. In “in vitro” and “in vivo” models of NSCLC (Non-Small Cell Lung Cancer), angiogenesis blockade has demonstrated an excellent anti-tumor activity, thus, a number of anti-angiogenic drugs have been approved by regulatory authorities for use in clinical practice. Much more interesting is the discovery of EGFR (Epithelial Growth Factor Receptor) mutations that predict sensitivity to the anti-EGFR Tyrosine Kinase Inhibitors (TKIs), a class of drugs that has shown to significantly improve survival when compared with standard chemotherapy in the first-line treatment of metastatic NSCLC. Nevertheless, after an initial response, resistance often occurs and prognosis becomes dismal. Biomolecular studies on cell line models have led to the discovery of mutations (e.g., T790M) that confer resistance to anti-EGFR inhibitors. Fortunately, drugs that are able to circumvent this mechanism of resistance have been developed and have been recently approved for clinical use. The discovery of robust intratumor lymphocyte infiltration in NSCLC has paved the way to several strategies able to restore the immune response. Thus, agents interfering with PD-1/PD-L1 (Programmed Death) pathways make up a significant portion of the armamentarium of cancer therapies for NSCLC. In all the above-mentioned situations, the basis of the success in treating NSCLC has started from understanding of the mutational landscape of the tumor.
Keywords: cancer related mortality